Integrasi Teknologi Informasi Dalam Rekrutmen Dan Seleksi Tenaga Kerja: Literatur Review - Fatah, Abdul; Hidayat, Mohammad Faricho Alvi; Adhim , Moh. Fauzil; Inayati, Titik (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Recruitment and selection is a crucial aspect of modern organizational management. The development of information technology has brought significant changes to the methods used by companies in recruiting and selecting prospective employees. This paper presents a literature review on the integration of information technology in the recruitment and selection process. in the human resource recruitment and selection process. Some of the innovations technology innovations analyzed include applicant tracking systems (ATS), the use of social media platforms, the utilization of data analytics, and the application of artificial intelligence. artificial intelligence. The findings of this study show that the application of technology technology can increase the speed and effectiveness of the recruitment process, expand access to potential candidates, and reduce the element of subjectivity. to potential candidates, as well as reducing the element of subjectivity. However, there are also a number of challenges, such as the risk of personal data leakage and ethical and fairness issues in the candidate screening process. as well as ethical and fairness issues in the candidate screening process. The article also provides some strategic suggestions to overcome these obstacles and maximize the role of technology in supporting the recruitment and selection process. and maximize the role of technology in supporting a more objective and efficient recruitment and selection process. process more objectively and efficiently.